2015
DOI: 10.1063/1.4937160
|View full text |Cite
|
Sign up to set email alerts
|

Airflow acceleration performance of asymmetric surface dielectric barrier discharge actuators at different exposed needle electrode heights

Abstract: The use of plasma, created by asymmetric surface dielectric barrier discharge (ASDBD), as aerodynamic actuators to control airflows, has been of widespread concern over the past decades. For the single ASDBD, the actuator performance is dependent on the geometry of actuator and the produced plasma. In this work, a new electrode configuration, i.e., a row of needle, is taken as an exposed electrode for the ASDBD plasma actuator, and the electrode height is adjustable. The effects of different electrode heights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Enloe's group [21,22] showed that the thrust was a linear function of the power consumption, which was confirmed by Kriegseis's study [23], and indicated that the electric field enhancement was a dominant factor for determining the effectiveness of momentum coupling into surrounding gas where the geometrical and electrical parameters played important roles in the force production. Hoskinson et al [6] demonstrated that different electrode shapes (cylindrical and rectangular shape) could result in different thrust and other authors [7][8][9] also studied the effect of electrode structures on mechanical performance and reached similar conclusions that field localized distribution was a vital factor for the increase of mechanical performance.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Enloe's group [21,22] showed that the thrust was a linear function of the power consumption, which was confirmed by Kriegseis's study [23], and indicated that the electric field enhancement was a dominant factor for determining the effectiveness of momentum coupling into surrounding gas where the geometrical and electrical parameters played important roles in the force production. Hoskinson et al [6] demonstrated that different electrode shapes (cylindrical and rectangular shape) could result in different thrust and other authors [7][8][9] also studied the effect of electrode structures on mechanical performance and reached similar conclusions that field localized distribution was a vital factor for the increase of mechanical performance.…”
Section: Introductionmentioning
confidence: 78%
“…Consequently, the effects of parametric variations that could lead to the amplification of charge density and field intensity (e.g. EE [6][7][8][9], dielectric materials (DMs) [10][11][12][13], applied voltage [14,15], surrounding condition [16,17]) have been studied, widely. However, both the charge distribution and interacting neutral flow field are strongly localized and unsteady, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…After 30 h of plasma discharge aging, for the pure PI actuator, as shown in Figure (b), it can be seen that in both positive and negative going cycle, the current pulses became much denser and had higher amplitudes, which might be caused by the accumulated charges of the filaments over the dielectric material in preceding half cycle of the applied voltage and enhanced electric field in the next half cycle. While for the PI/Al 2 O 3 actuator shown in Figure (d), the amplitudes of current pulses only slightly increased in the positive‐going cycle, suggesting that after plasma discharge aging, the charge accumulation on the surface was not as serious as the case of the pure PI actuator, which was beneficial to the thrust production in active flow control . During the negative‐gong cycle, the change was not apparent either.…”
Section: Results and Analysismentioning
confidence: 99%
“…Plenty of reports have investigated the performances of the plasma actuators for a variety of parameters including exposed electrode shape, electrode length or width, material permittivity, voltage waveform, pressure, and so on. Although the produced body force or induced flow velocity has been optimized and enhanced, attentions to their robustness during the long plasma processing are far from adequate at present.…”
Section: Introductionmentioning
confidence: 99%
“…As the result of plasma-accelerated ion interactions with the air neutral molecules, the momentum transfers to the surrounding air and a secondary flow, which is called the ionic wind or electric wind, will be induced. The effect of ASDBD in injecting momentum to the flow is noticeable in aerodynamic flow control applications, so a lot of experimental and numerical studies have been done to improve its operation efficiency [8][9][10][11][12]. Porter et al [13] investigated the phenomenology of the momentum transfer to air by measuring the temporal and time averaged body force.…”
Section: Introductionmentioning
confidence: 99%